A comparison study on thermal performance enhancement of corrugated oil cooler with internal turbulators – Numerical and experimental approach. (2022) - Vijayaraghavan, S.; Shah, Rohan; Vinoth Kumar, D.
Abstract: Oil coolers play an important role in dissipating excess heat from engine oil to surroundings. In this work, performance study of an oil cooler with internal turbulators of dimple and offset type is performed using numerical approach and compared with experimental results for validation. In numerical approach, oil cooler with turbulators are numerically modeled using Conjugate Heat Transfer (CHT) approach to solve for heat transfer characteristics. Turbulence physics modeling is done using Reynolds Averaged Navier Stokes equations (RANS) through realizable k-epsilon model with standard wall function. The air side Heat Transfer Coefficient (HTC) estimation is done with CHT model using one corrugation, as the air flow in fins is periodic. In experimental study, Required Inlet Temperature Difference (ITD), Oil Flow Rate, Air Flow Rate is maintained, measurements are recorded to create performance data matrix with combinations of various operating data points for air and oil sides respectively. Numerical results are compared with experimental results obtained; Deviation for heat rejection of oil-cooler with dimple turbulator fall in range of ±7%, offset turbulator fall in the range of −2.0 to 9.4%. Numerical data shows that the thermal performance of offset type is better than dimple type by 10–13.5%, while the test data depicts that performance of oil-cooler with offset turbulator is high by 12–19% than dimple type and thereby proving its performance superiority. In offset turbulator additional turbulent scales of the offset length scale range are generated, these additional scales are evident by increasing the Turbulent Kinetic Energy (TKE) of 46–51% than dimple turbulator from numerical study. Thus, for same plate and fin, oil-cooler with offset turbulator has better thermal performance than oil cooler with dimple turbulator.